1997
DOI: 10.1021/ja972603p
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Stipiamide and Designed Polyenes as New Agents for the Reversal of Multidrug Resistance

Abstract: The synthesis of (−)-stipiamide (1) is reported together with the designed enynes 2 (6,7-dehydrostipiamide) and 3 that are now shown to reverse the multidrug resistance (MDR) of human breast cancer cells (MCF-7adrR). Stipiamide was assembled using a Stille coupling with (E)-vinyl iodide 17 and (Z)-stannyl amide 16 in 78% yield. (E)-Vinyl iodide 17 was made using a Takai reaction and a selective dihydroxylation of the terminal olefin of nonconjugated diene 7 using the Sharpless AD-mix reagent. The precursor to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…5 A common building block for the synthesis of the phenalamides is the aldehyde 6. 1,5,6 We describe here our route to generate this aldehyde 6, using an allylation with the chiral (E)-a-chlorocrotylboronate (4) as key step to create the stereogenic centers at C-12 and C-13 (phenalamide numbering) (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A common building block for the synthesis of the phenalamides is the aldehyde 6. 1,5,6 We describe here our route to generate this aldehyde 6, using an allylation with the chiral (E)-a-chlorocrotylboronate (4) as key step to create the stereogenic centers at C-12 and C-13 (phenalamide numbering) (Scheme 2).…”
Section: Methodsmentioning
confidence: 99%
“…This seemingly simple transformation was quite difficult, giving a poor yield of 40% when carried out in THF. Andrus 6 used toluene at 90°C for the same transformation and obtained 55% of an 8:1 E:Z-mixture of 14. We found that the reaction carried out in refluxing CH 2 Cl 2 or in benzene at r.t. is higher yielding (93% to 96%) and furnishes product 14 free of the corresponding Z-isomer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional coupling conditions ([Pd(PPh 3 ) 4 ], CuI, n BuNH 2 in benzene)22 failed to generate any of the desired product 29 . However, conditions developed for the coupling of electron defficient alkynyl amides23 [(Ph 3 P) 2 PdCl 2 ], CuI, i Pr 2 NH, in ethyl acetate) proved successful, affording the protected aglycon 29 in 93 % yield with retention of double bond geometry. Finally, deprotection of the TBS ether with TBAF, followed by treatment with catalytic PPTS in wet acetonitrile to hydrolyse the methyl acetal, provided the callipeltoside aglycon 30 .…”
Section: Methodsmentioning
confidence: 99%
“…[97] made a vinylidene dibromide moiety react with the required vinyltin; the coupling was immediately followed by HBr elimination (Scheme 6.32); Trost et al [98] The more conventional vinyl-vinyl coupling methodology has been used in a total synthesis of stipiamide [99], for the completion of the side chain in a total synthesis of (−)-pateamine A [100], and in attaching the tetraenyl moiety (from the tin component) in syntheses of retinoic acid and some ring-modified analogs thereof [101]. A catalyst system first used by Negishi [102] a quarter of a century ago [(Ph 3 P) 2 PdCl 2 /Dibal-H] (Dibal-H, diisobutylaluminum hydride) was employed [103] in the completion of the lower side chain in (+)-manumycin A.…”
Section: Vinyl-vinyl Couplingsmentioning
confidence: 99%